Centre sampling for estimating elusive population size - Monica Pratesi; Emilia Rocco (Statistica, 2007)
The estimation of the size of an elusive population is a problem frequently addressed in many fiels of applications. In the paper a sampling strategy for the estimation of the size is proposed, the properties of the estimator are evaluated in a design-based approach. The estimator is unbiased, admissible and consistent and the design is measurable. The expressions of the variance of the population size estimator and of its unbiased sample estimator are also proposed. The strategy is applied to a simulated population.